Study of the Rainfall Rate in Iraq - Karem, Sajad Ali Ismail; Jassim, Ali Khalaf Ali; Atia, Mariam Mohammed Abdulhamza; Abdullah, Meaad Khaled Hamad (American Journal of Biodiversity, 2024)
The research aims to shed light on the rates of rain falling on Iraq, as well as the amounts of rain between one region and another, and one direction and another. Our research targets the southern, central, and northern governorates, as the southern governorates suffer from a scarcity of rain during periods of drought and certain months of high temperatures and relative to moderate rain in Winter and the central governorates as well. As for the northern regions, they may flourish more than other regions in terms of rainfall rates, as they are the highest. Comparisons and numbers about rainfall rates were included in the research. They were extracted from a site and were studied in detail in the research. The research also reviewed the importance of rain and the devices used in measuring quantities. Falling rain: (Rain measuring devices Float rain recorder) We aim to study Arthmatic Method: One method is to calculate the arithmetic mean. To do this, add up all the values and divide the sum by the number of values.